“My Company Is Friendly,” “Mine’s a Rebel”: Anthropomorphism and Shifting Organizational Identity From “What” to “Who” - Ashforth, Blake E.; Schinoff, Beth S.; Brickson, Shelley L. (Academy of Management Review, 2020)
Why don’t we blink when our organizations are described as friendly or aggressive? Why do we expect our organizations to care about our well-being? We argue that anthropomorphism—an attribution of human qualities or behavior to nonhuman entities, objects, and events—is both pervasive and surprisingly important in organizational life. Anthropomorphism helps satisfy the motives for sensemaking and social connection, even if the veracity of the results is in the eye of the beholder. Although anthropomorphism has broad relevance to various domains, we primarily focus on organizational identity. We contend that anthropomorphism enables organizational members to conceive of their organization in terms of “who it is/who we are as an organization” (e.g., personality, attitudes, affect), rather than “what it is/what we are” (e.g., industry, structure, age). This shift facilitates a more visceral, memorable, and energizing organizational identity, with major implications. We discuss how anthropomorphism results from both top-down (i.e., “This is who we are”) and bottom-up (i.e., “You appear human to me”) dynamics. We also discuss how treating an organization as if it were a person primes “interpersonal” emotions, behaviors, and accountability and facilitates social, relational, and personal identification—as well as a psychological contract—with the organization.